Learning Model of Literary Sociology with Contextual and Spiritual Quotient(CSQ) Approach - Masnuatul Hawa; Andayani, Andayani; Suyitno, Suyitno; Nugraheni Wardani (Proceedings of the 1st International Conference on Science and Technology for an Internet of Things, 2018)
The course of Literary Theory is a basic course in the field of literature in Indonesian Language Education Study Program. This course is an introduction to analyzing Indonesian literature that discusses the main points of literary theory along with the background of thought that influences theoretical concepts. Literary Sociology is one of the subjects inherent in the study of literary subjects in Indonesian Language Education Study Program in Higher Education context. Learning literary theory, especially the Literary Sociology theory, is still considered boring for most students, therefore, presenting a model of learning with CSQ approach is considered very important to make students active, creative, happy, and have spiritual characters. This research wasa part of Doctoral dissertation research. The purposes of this research were to describe and explain the learning of Literary Sociology theory with CSQ approach. The subject of this research was the students of Indonesian Language Education Study Program. The result of the research shows that learning Literary Sociology theory using CSQ approach can make the students active, creative, joyful, and have spiritual characters indicated by the ability to (1) construct; (2) ask; (3) inquiry; (4) learn in community; (5) have modeling; (6) have reflection; (7) use authentic assessment.